2015
DOI: 10.1016/j.nanoen.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the oxygen reduction on nitride stabilized pt-M (M=Fe, Co, and Ni) core–shell nanoparticle electrocatalysts

Abstract: Given the harsh operating conditions in hydrogen/oxygen fuel cells, the stability of catalysts is one of the critical questions affecting their commercialization. We describe a distinct class of oxygen reduction (ORR) core-shell electrocatalysts comprised of nitride metal cores enclosed by thin Pt shells that is easily synthesized. The synthesis is reproducible and amenable to scale up. Our theoretical analysis and the experimental data indicate that metal nitride nanoparticle cores could significantly enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 34 publications
4
96
0
Order By: Relevance
“…Although the exact species of NiNx could not be determined, the XAS results along with the STEM-EELS analysis indicate that Ni in the core-shell structured PdNiN nanoparticles is nitrided. Our previous studies on nitrided Pt-M (M = Ni, Fe or Co) core-shell nanoparticles have indicated the presences of M4N species [22,23]. As the synthesis parameters are similar to the previous study we presume the presence of Ni4N species in our PdNiN core-shell nanoparticles.…”
Section: Resultssupporting
confidence: 84%
“…Although the exact species of NiNx could not be determined, the XAS results along with the STEM-EELS analysis indicate that Ni in the core-shell structured PdNiN nanoparticles is nitrided. Our previous studies on nitrided Pt-M (M = Ni, Fe or Co) core-shell nanoparticles have indicated the presences of M4N species [22,23]. As the synthesis parameters are similar to the previous study we presume the presence of Ni4N species in our PdNiN core-shell nanoparticles.…”
Section: Resultssupporting
confidence: 84%
“…Bi‐functional catalysts, capable of driving both reactions, for example in unitized regenerative fuel cells (URFC), demand the development of reliable catalyst materials that are abundant and cheap . Presently, well known catalysts for ORR and OER are precious metals or their alloys, and precious metal oxides . Considering the high cost and scarcity of precious metals, a number of alternative earth abundant materials such as transition metal (e.g., Fe, Ni, Co, and Mn) oxides, sulfides, phosphides, and nitrides/borides have been introduced into the field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the researchers here also predicted that higher N concentrations may facilitate further Pt diffusion and therefore increased durability [544]. Later, Adzic et al [545] again reported that core-shellstructured FeN@Pt and CoN@Pt catalysts synthesized by using the same method also showed good ORR catalytic activities and high cycling stabilities. Moreover, using DFT calculations, these researchers predicted that NiN@Pt can produce the highest ORR activity among NiN@Pt, CoN@Pt, and FeN@Pt catalysts because FeN and CoN cores impart higher compressive strains to Pt shells than NiN cores, which only provide a slight but moderate compressive force to the Pt shell.…”
Section: Nitrides As Corementioning
confidence: 52%
“…However, many problems still exist for TMN core applications. For example, according to previous reports [544,545], in TMN cores comprised of two phases, more research is required to determine which phase contributes more to Pt shell performances, and which synthesis parameters need to be controlled to obtain TMNs with one pure phase. And because of this, significant efforts are still required before TMNs can be widely applied as cores for electrocatalysis (Fig.…”
Section: Nitrides As Corementioning
confidence: 99%